The sons of Cain - Chopín, Juan Vicente (Teoría y Praxis, 2012)
This article deals with the city from an anthropological, biblical and theological point of view. First of all, it highlights the current situation of the inhabitants of the city, particularly the fear they feel. Secondly, it presents the city as an area of the mission of the Church. TEORÍA Y PRAXIS Year 10, No.21, June-December 2012, pp.37-56